(untitled) (Fiep Bulletin - online, 2014)
Introduction: High body mass index in thoracoabdominal compartment promotes changes in respiratory system interfering in volumes and capacities e and consequently in gas change. Objective: To analyze comparatively the thoracoabdominal mobility relating to children body mass index. Methodology: It is a transversal study with quantitative and descriptive approaching. The sample counted with 70 children with ages of 8 to 12 years of both genders, and with variable body mass index. It was carried out a children weight, height and expansibility verification and after classified in three groups according to their body mass indexes: eutrophic (57,1%), with overweight (15,7%) and obese (27,1%). Results: The results obtained presented differences of the eutrophic and obese group indicating, in this perspective, that the mobility in axillar region xifoidea are greater in the eutrophic group when compared to the obese one. Conclusion: Therefore, it is concluded that the body mass index is related to children thoracoabdominal expansibility changes.